2021
DOI: 10.12998/wjcc.v9.i36.11156
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum Sestrin2 level and diabetic peripheral neuropathy in type 2 diabetic patients

Abstract: BACKGROUND Diabetic peripheral neuropathy (DPN) is a chronic and serious microvascular complication of diabetes linked to redox imbalance. Sestrin2, a novel inducible stress protein, participates in glucose metabolic regulation and redox homeostasis. However, the association between serum Sestrin2 and DPN is unknown. AIM To explore the association between serum Sestrin2 and DPN in patients with type 2 diabetes mellitus (T2DM). METHODS A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Evidence has shown that SESN2 is of great clinical significance in a variety of diseases. Circulating SESN2 levels have been identified viable in indicating disease severity or prognosis, including cardiovascular diseases [ 117 119 ], respiratory diseases [ 120 , 121 ], neurodegenerative diseases [ 122 , 123 ], metabolic diseases [ 124 , 125 ], cancers [ 106 , 126 ], etc. Since SESN2 expression is dynamically changed during liver pathology, we hypothesize that SESN2 has a good potential as a clinical biomarker and prognostic indicator for liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that SESN2 is of great clinical significance in a variety of diseases. Circulating SESN2 levels have been identified viable in indicating disease severity or prognosis, including cardiovascular diseases [ 117 119 ], respiratory diseases [ 120 , 121 ], neurodegenerative diseases [ 122 , 123 ], metabolic diseases [ 124 , 125 ], cancers [ 106 , 126 ], etc. Since SESN2 expression is dynamically changed during liver pathology, we hypothesize that SESN2 has a good potential as a clinical biomarker and prognostic indicator for liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Mao et al. conducted a clinical study and documented that serum Sestrin2 is lowered in T2DM patients with diabetic peripheral neuropathy ( 128 ).…”
Section: The Roles Of Sestrin2 In Diabetic Complicationsmentioning
confidence: 99%